Corpul ca poveste: dansul ca formă de narațiune emoțională și fizică - Olar, Cristina Maria (Symbolon, 2025)
Body as Story: Dance as a Form of Emotional and Physical Narrative Body as Story explores how dance transforms movement into a narrative language as a way of exploring and conveying human experiences. The aesthetic function of dance transcends bodily barriers and transforms into a form of emotional communication in which the body becomes the protagonist of the narrative, narrating through movement the same conflicts, emotions and situations that are usually expressed in words. Performances by choreographers such as Pina Bausch, Merce Cunningham, William Forsythe, Anna Teresa De Keersmaeker, Sidri Larbi Cherkaoui, Gigi Căciuleanu, etc. have shown how movement can create an atmosphere of introspection, where time, space and rhythm are used to reflect the inner realities of the characters. Thus, dance becomes not just a physical act, but a narrative device that opens up new ways of understanding the human experience, where the body is both the messenger and the story. Choreographers create characters and stories through the dancer's body, and each movement says something about their inner feelings. In both choreographic and theatrical performances dance plays an important role in facilitating the psychological exploration of the characters, building conflicts, resolving them or intensifying the message intended for the audience. Through movement, the body becomes a fundamental element in the construction of dramaturgy, sometimes even possessing a textual function.